Management of Type 1 Diabetes in a school setting: effectiveness of an online training program for school staff - Bassi, Marta; Scalas, Marta; Spacco, Giordano; Perasso, Viola; Franzone, Daniele; Strati, Marina Francesca; Dufour, Francesca; Lionetti, Barbara; Rizza, Francesca; Parodi, Stefano; d’Annunzio, Giuseppe; Minuto, Nicola (Frontiers in Public Health, 2024)
Background and aims: Since Type 1 Diabetes (T1D) onset usually occurs at a young age, a relevant number of affected people attend school for most of their time; it is necessary that school personnel receive appropriate education and training. We aimed to evaluate the effectiveness of the online training program offered by IRCCS Istituto Giannina Gaslini during and after Covid-19 pandemic. Methods: The Institute's Diabetes team offered an online training program to school staff of the Region during Covid-19 pandemic. A validated questionnaire was proposed to all the schools in which training meetings were held in the previous two years (2020-2021 and 2021-2022). The questionnaire consisted of 4 sections: Section 1 (Socio-demographical data), Section 2 (Theoretical knowledge on T1D), Section 3 (Confidence in handling T1D) and Section 4 (Practical skills and Glucagon Administration). To evaluate the effectiveness of the online training program the answers between participants (Group A) and non-participants (Group B) were then compared. Results: 225 subjects from 19 schools participated in the survey. People who participated to the training (Group A, n=53) demonstrated better T1D theoretical knowledge compared to nonparticipants (Group B, n=154) (p<0.001). Group A revealed to feel more confident in the management of children with T1D during scholastic (p=0.006) and extra-scholastic activities (p=0.01), in supporting the children in the administration of insulin (p<0.001) and in recognizing hypoglycaemia (p=0.006). Moreover, results confirmed good levels of confidence among scholastic personnel who participated in the training of administration of glucagon in case of severe hypoglycaemia. Conclusions: School staff who took part in the online training program on management of T1D showed better theoretical knowledge and better confidence in the management of daily needs and possible emergencies of students with T1D. The training program resulted effective in granting a safer scholastic environment and probably increase the feeling of safety in children with T1D and their parents. It appears essential to offer educational programs on T1D for school staff by implementing the use of technological tools to reach a wider population. Moreover, it is advisable to offer a more practical approach, involving educational nurses.